العقلانية في الشعر العربي ( المعري كأنموذج ): Reason or Rationality in Arabic poetry. ( in light of Muarri’s poetry ) (Khairulummah, 2023)
This article has been written about the life and educational services of the Poet Abu Ula-Al Muarri, and the circumstances  of life of the poet have been narrated in the article here it has been mentioned  pertaining to his life. Things have been  told regarding his lineage, his region and the reasons of his title. The incident of his childhood intelligence have been  narrated in this article. Also, it has been indicated about poets he has studied. Apart from that, it has also been told in the article how treated  with his  poetry, and how he earned fame. This  article has covered the account of a great poet, in short  period and on  limited  pages. If we go through these  few points, we can bring to the surface the important aspects of his whole life.Hence, it is a unique and conspicuous article.